CONGENITAL THUMB HYPOPLASIA IN CHILDREN: TYPE II AND III ACCORDING TO THE BLAUTH CLASSIFICATION – DIFFERENTIATION AND TREATMENT TECHNIQUES (Vietnam Journal of Community Medicine, 2026)
To evaluate methods for accurately distinguishing between Type II and Type III thumb hypoplasia according to the Blauth classification based on clinical and radiographic findings, and to assess the outcomes of treatment techniques applied to pediatric patients with congenital thumb hypoplasia treated at the Ho Chi Minh City Hospital of Trauma and Orthopedics.Materials and Methods:A prospective descriptive case series conducted from 2022 to 2025 at the Pediatric Orthopedics Department of the Ho Chi Minh City Hospital of Trauma and Orthopedics, including pediatric patients with Type II and Type III thumb hypoplasia according to Blauth classification.Results:A total of 8 cases of Type II and Type III thumb hypoplasia were surgically treated. The mean age at the time of surgery was 5.62 years. Among them, there were 2 cases of Type II and 6 cases of Type III (according to the modified Manske classification: 4 cases of Type IIIA and 2 cases of Type IIIB). Treatment methods included opponensplasty (Huber, Riordan techniques), ulnar collateral ligament reconstruction, and metacarpal bone grafting from the foot. Functional outcomes assessed using the James scoring system showed 4 good, 1 fair, 2 average, and 1 poor result.Conclusion:Differentiating between Type II and Type IIIA thumb hypoplasia remains challenging in young children due to unclear clinical and imaging features. Careful evaluation of the trapeziometacarpal joint function and the thenar muscle group plays a decisive role in diagnosis and in selecting appropriate treatment methods.
Keywords: Thumb hypoplasia, Blauth, Manske, pediatric hand surgery.